Monoclonal Antibodies to Human Cell Surface Antigens - Beare, Alice (Curr Protoc Immunol, 2008)
Many of the leukocyte cell surface molecules are known by “CD” numbers. In this Appendix, a short introduction describes the history and the use of CD nomenclature and provides a few key references to enable access to the wider literature. This is followed by a table that lists all human molecules with approved CD names, tabulating alternative names, key structural features, cellular expression, major known functions, and usefulness of the molecules or antibodies against them in research or clinical applications. Curr. Protoc. Immunol. 80:A.4A.1‐A.4A.73. © 2008 by John Wiley & Sons, Inc.